1988
DOI: 10.2527/jas1988.664939x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Preovulatory Endocrine Events, Estrus and Ovulation in Brahman × Hereford Females Synchronized with Norgestomet and Estradiol Valerate

Abstract: The purpose of these studies was to investigate the pattern and timing of preovulatory endocrine events, estrus and ovulation in Brahman X Hereford (F1) heifers synchronized with norgestomet and estradiol valerate. In Exp. 1, 66 nulliparous and 191 primiparous Brahman X Hereford (F1) heifers were used to estimate the interval from norgestomet implant removal to onset of estrus. The mean interval from implant removal to onset of estrus was 29.8 +/- .5 h, with 80.9% exhibiting estrus within 48 h. Endocrine and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 19 publications
0
15
1
1
Order By: Relevance
“…The earlier onset of behavioral estrus after norgestomet removal in females in the PG 7 group as compared to those in the PG 17 group probably occurred as a result of the more advanced stage of the ovarian follicles in females in the PG 7 group at the time of treatment removal [22]. Earlier reports indicate that estrus occurs within 48 h of norgestomet withdrawal [5]. We have previously reported that the preovulatory surge of LH occurs earlier subsequent to norgestomet withdrawal than in cows that have had their CL lysed with PGF 2 [8].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The earlier onset of behavioral estrus after norgestomet removal in females in the PG 7 group as compared to those in the PG 17 group probably occurred as a result of the more advanced stage of the ovarian follicles in females in the PG 7 group at the time of treatment removal [22]. Earlier reports indicate that estrus occurs within 48 h of norgestomet withdrawal [5]. We have previously reported that the preovulatory surge of LH occurs earlier subsequent to norgestomet withdrawal than in cows that have had their CL lysed with PGF 2 [8].…”
Section: Discussionmentioning
confidence: 84%
“…It has been suggested that lowered pregnancy rates after treatment with norgestomet may be due to an improper temporal relationship among estrus, the preovulatory surge of LH, and ovulation [4]. In another study, delayed selection and/or maturation of the ovulatory follicle were implicated as factors involved in reduced fertility when norgestomet was used to synchronize estrus in cows [5]. In addition, reduced fertility in cows in which time of estrus is synchronized with norgestomet may result from aberrant uterine function [6].…”
Section: Introductionmentioning
confidence: 95%
“…Wiltbank and Gonzalez Fadilla (1975), Short et al (1976) and Humphrey et al (1977) used single Norgestomet implant in combination with estradiol valerate to control estrous-cycle length. The incidence of synchrony of estrus following the above treaftnent is high (Miksch et al 198;Spitzer et al 1978 (Rentfrow et al 1987;Mikeska and Williams 1988). In a recent study (Taylor et al 1993), based on a small number of observations, we showed that prolonged maintenance of the dominant follicle with single Norgestomet implant is not detrimental to conception rate.…”
mentioning
confidence: 58%
“…An LH surge was defined as an increase in LH concentrations over the level of the baseline plus at least two times the SD that subsequently remained elevated in at least two consecutive samples collected at 3 h intervals [25]. The baseline was obtained as the mean concentration of the samples collected for 48 h before administration of Dose-2 E 2 B.…”
Section: Methodsmentioning
confidence: 99%